HUBUNGAN PENGETAHUAN TENTANG PENGUMUMAN DENGAN KETERAMPILAN MENULIS PENGUMUMAN SISWA KELAS VII SMP NEGERI 16 PADANG - Sari, Novita; Emidar, Emidar; Arief, Ermawati (Universitas Negeri Padang, 2018)
The purpose of this study consists of three things as follows. First, describe the knowledge about the level of ability of the announcement of class VII students of SMP Negeri 16 Padang. Second, describe the level of writing skill of class VII SMP Negeri 16 Padang. Third, analyze the relationship of knowlagde about the announcement with the skill of writing the data of class VII student of SMP Negeri 16 Padang. This research type is quantitative research with descriptive method. The design of this research is correlational design. The population in this study is the students of class VII of SMP Negeri 16 Padang registered in the academic year 2016-2017. The sample in this research by using random sampling technique. The variable of this research is knowlagde of announcement as variable X (indenpendent variable) and writing achievement as variable Y (dependent variable). The data of this research is score of knowlagde test result about student announcement of class VII SMP Negeri 16 Padang and score of skill test result of student data of class VII SMP Negeri 16 Padang. Kata kunci: hubungan, pengetahuan tentang pengumuman, menulis pengumuman.